An Eocene/Oligocene blueschist‐/greenschist facies P–T loop from the Cycladic Blueschist Unit on Naxos Island, Greece: Deformation‐related re‐equilibration vs. thermal relaxation. (2nd July 2017) - Peillod, Alexandre; Ring, Uwe; Glodny, Johannes; Skelton, Alasdair
Abstract: Geothermobarometric and geochronological work indicates a complete Eocene/early Oligocene blueschist/greenschist facies metamorphic cycle of the Cycladic Blueschist Unit on Naxos Island in the Aegean Sea region. Using the average pressure–temperature ( P–T ) method ofthermocalc coupled with detailed textural work, we separate an early blueschist facies event at 576 ± 16 to 619 ± 32°C and 15.5 ± 0.5 to 16.3 ± 0.9 kbar from a subsequent greenschist facies overprint at 384 ± 30°C and 3.8 ± 1.1 kbar. Multi‐mineral Rb–Sr isochron dating yields crystallization ages for near peak‐pressure blueschist facies assemblages between 40.5 ± 1.0 and 38.3 ± 0.5 Ma. The greenschist facies overprint commonly did not result in complete resetting of age signatures. Maximum ages for the end of greenschist facies reworking, obtained from disequilibrium patterns, cluster near c . 32 Ma, with one sample showing rejuvenation at c . 27 Ma. We conclude that the high‐ P rocks from south Naxos were exhumed to upper mid‐crustal levels in the late Eocene and early Oligocene at rates of 7.4 ± 4.6 km/Ma, completing a full blueschist‐/greenschist facies metamorphic cycle soon after subduction within c . 8 Ma. The greenschist facies overprint of the blueschist facies rocks from south Naxos resulted from rapid exhumation and associated deformation/fluid‐controlled metamorphic re‐equilibration, and is unrelated to the strong high‐ T metamorphism associated with the Miocene formation of the Naxos migmatite dome. It follows that the Miocene thermal overprint had no impact on rock textures or Sr isotopic signatures, and that the rocks of south Naxos underwent three metamorphic events, one more than hitherto envisaged.